Global Economic Prospects, January 2017 : Weak Investment in Uncertain Times - World Bank Group (Washington, DC: World Bank, 2017)
Stagnant global trade, subdued investment, and heightened policy uncertainty marked another difficult year for the world economy. A subdued recovery is expected for 2017, with receding obstacles to activity in commodity exporters and solid domestic demand in commodity importers. Weak investment is weighing on medium-term prospects across many emerging markets and developing economies (EMDEs). Although fiscal stimulus in major economies, if implemented, may boost global growth above expectations, risks to growth forecasts remain tilted to the downside. Important downside risks stem from heightened policy uncertainty in major economies.